3D game programming for kids : create interactive worlds with JavaScript - Strom, Chris (Pragmatic programmers., 2018)
You know what's even better than playing games? Programming your own! Make your own online games, even if you're an absolute beginner. Let your imagination come to 3D life as you learn real-world programming skills with the JavaScript programming language - the language used everywhere on the web. This new edition is completely revised, and takes advantage of new programming features to make game programming even easier to learn. Plus, new effects make your games even cooler. When you're done, you're going to be amazed at what you can create. Jump right in! Start programming cool stuff on page 1. Keep building new and different things until the very last page. This book wants you to play. Not just play games, but play with code. Play with programming. Because the best way to learn something is to have fun with it! This second edition is updated from start to finish to make it even easier to get started programming in JavaScript. Every example has been updated to make it easier, with new example games to explore and new 3D effects that make your games even more fun! Want a red donut? You can make hundreds of them, spinning around like mad. Want to create a star field? Make a hundred or a thousand stars. Make them red, green, or blue. Explosions? Fireworks? Planets? It's up to you. And, using a code editor created especially for this book, you'll program right in your web browser. You'll see the results of your work and imagination right away - right next to the code that you just typed! Along the way, you'll pick up a ton of programming knowledge, and dive in even deeper with some more advanced chapters. Whatever you want to do, this book has your back. Best of all, you get to create awesome games and say, "I made this!" What You Need: You need the latest version of the Google Chrome Web browser, available for free from https://chrome.google.com . You also need an Internet connection to access the ICE Code Editor the first time. ICE Code Editor will be loaded onto your computer, so you won't need Internet access for later projects.